«DEMONIC MIRACLES» OF THE MAGUS AND THE AFFAIRS OF THE RIGHTEOUS IN THE RUSSIAN PRIMARY CHRONICLE - A. Novoselov (Гуманитарные и юридические исследования)
The article discusses the place and meaning of the stories about miracles in the Tale of Bygone Years, which are the stories of unexpected, supernatural events that occur at the will of God and solve some earthly problems. The miracle is a genre of Old Russian literature, found mainly in the hagiography. The specificity of miracles as stable literary elements in chronicles is their polysemanticism, acquired in interaction with other parts of the annalistic text. Wonders are an integral part of the picture of the world of the Old Russian inhabitants, and therefore the study of the representation of the phenomenon of "miracle" in annalistic texts is important and necessary to reconstruct the mentality and everyday practices of these people. The marker of "miraculous" in the Tale of Bygone Yearsis an emotionally loaded description of an event that caused surprise or curiosity. The article shows the ways of representation and the role of the "miraculous" in the text of the Tale of Bygone Years, preserved in the Laurentian, Ipatiev, Radzivilov, Novgorod first (senior and junior) chronicles. The 'miraculous' as a part of the 'wondrous' is regarded as a symbolic expression of the idea of manifestation of divine power and divine will through the Magi, the monks of the Kiev Pechersk Monastery, and the first Russian saints Boris and Gleb, proposed by the conditional author of the Tale of Bygone Years. It is proved that in the Tale of Bygone Years, there is an opposition to the wonders of the magi by attributing to the magi the features of biblical false prophets and emphasizing the "unsurprising" of their miracles. This can be explained by the fact that the preceding Story of the Time Years of Chronicles was compiled under the impression of the Rostov uprising of 1071, led by the Magi from Yaroslavl. An attempt was made to reveal textual connections of annalistic miracles with famous sources of the Tale of Bygone Years: the Chronicle of George Amartol, the Revelation of Methodius of Pattar, translated (The Life of Basil the New) and Old Russian hagiographic works (Kiev-Pechersk Paterik, the Tale of Boris and Gleb), books of the Old and New Testaments. The possibilities of applying interdisciplinary methods in the study of Old Russian historical sources are revealed.